Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
PURPOSE: MUC-16-targeted antibodies can deliver contrast agents (diagnostic) and/or cytotoxic payloads (therapy) to the tumor site. MUC-16 is overexpressed in 80% of epithelial ovarian cancer (EOC) and 65% of pancreatic ductal adenocarcinomas (PDAC). We previously developed a fully human antibody against MUC-16 (M16AB) and demonstrated the utility of [89Zr]Zr-DFO-M16AB as a PET imaging agent. Here, we developed [225Ac]Ac-Macropa-M16AB radioimmunoconjugate (RIC) and studied its efficacy against MUC-16-positive EOC and PDAC xenografts. EXPERIMENTAL DESIGN: [225Ac]Ac-Macropa-M16AB was characterized in vitro. The pharmacokinetics, biodistribution, hematological safety and dosimetry of [225Ac]Ac-Macropa-M16AB were studied in healthy mice. The efficacy of two doses (13 or 18.6 kBq) [225Ac]Ac-Macropa-M16AB administered at 10 days apart was evaluated in MUC-16-expressing cell line-derived xenograft (CDX) SW1990 and mice bearing PDAC and EOC patient-derived xenografts (PDX) with varying MUC-16 expression levels. RESULTS: In SW1990 CDX models [225Ac]Ac-Macropa-M16AB induced complete remission (CR) in 16.7% of mice, while the remaining 83.3% exhibited durable tumor growth suppression for ≥ 50 days, whereas all control animals progressed rapidly. [225Ac]Ac-Macropa-M16AB treatment resulted in 100% sustained CRs in high and medium-MUC16-expressing EOC and PDAC PDXs. While in the low MUC-16 expressing EOC PDX, the treatment demonstrated tumor growth inhibition and prolonged survival. [225Ac]Ac-Macropa-M16AB (3 x 15 kBq) administered in naive mice, 10-d apart was tolerated biochemically and haematologically, with only mild, dose-dependent hepatic and splenic changes observed on histopathology. CONCLUSION: The effectiveness of[225Ac]Ac-Macropa-M16AB which is dependent on the expression levels of MUC-16 indicates potential benefits for EOC and PDAC patients when translated in clinical trials.